Analisis Kondisi Fisik Atlet Putri Pencak Silat Kategori Tanding Ekstrakurikuler Usia 15-16 Tahun SMA Negeri 12 Surabaya - Yuliana, Arini; Wahyudi, Heri (Faculty of Sport and Health Sciences, 2022)
This time, to be an international athlete and achiever must have a very good physique. Especially in the sport of pencak silat, physical condition is the initial benchmark to support technical, tactical, and strategy training. This study aims to determine and analyze the physical condition of female athletes of pencak silat in the extracurricular competition category aged 15-16 years at SMA Negeri 12 Surabaya. This research will use descriptive quantitative research which describes the physical condition of female athletes of extracurricular pencak silat aged 15-16 years at SMA Negeri 12 Surabaya. The population in this study were all female pencak silat athletes who joined the pencak silat extracurricular at SMA Negeri 12 Surabaya as many as 6 people. This research data collection instrument used tests and measurements with several test items such as strength, speed, agility, balance, and endurance with a total sample of 6 female athletes of extracurricular pencak silat SMA Negeri 12 Surabaya. The data analysis technique used by the researcher is the univariate technique to determine the physical condition of the athlete and the bivariate technique to determine whether the athlete's physical condition is good or not.